Eletrodo de diamante dopado com boro para a determinação voltamétrica/amperométrica de antihelmínticos e anti-hipertensivos - Lourenção, Bruna Cláudia (2014)
In this work it was developed, firstly, one method for determination of anthelmintic albendazole (ABZ) using differential pulse voltammetry (DPV) and the boron doped diamond (BDD) electrode catholically pretreated (BDD-CPT). The corresponding analytical curve showed linear response in the concentration range from 0.08 to 8.36 ^mol L-1 with detection limit (LD) of 0.06 ^mol L-1. The proposed method was applied in the determination of ABZ in three pharmaceutical formulations with similar results those obtained using a comparative method. The second part of this work it was to develop two electroanalytical procedures using the amperometry technique coupled to a flow injection analysis system (FIA) for the individual determination of two anthelmintic, the ivermectin (IVM) and levamisole (LVM), where it was used the BDD electrode anodically pretreated (BDD-APT) for LVM and BDD-CPT for IVM. Good linear ranges were obtained for the respective analytical curves with values of 0.60 to 50.0 ^mol L-1 for IVM and 0.01 to 6.00 ^mol L 1 for LVM with LD of 0.30 ^mol L 1 and 1.0 nmol L 1, respectively. These analytes were determined in samples of commercial pharmaceutical formulations and synthetic urine and the results obtained are in agreement with the results obtained using two comparative methods (one for each analyte). The analytical frequencies for each method were 48 and 56 determinations per hour for IVM and LVM, respectively. Another procedure was developed for simultaneous determination of two anthelmintics LVM and albendazole sulfoxide (ABZ-SO) in synthetic urine samples using a FIA system with multiple pulses amperometry (MPA) detection and the BDD-APT electrode. This method was applied for directly determination of ABZ-SO and for indirectly determination of LVM. The employed sequence of dual-potential waveform as a function of time, previously optimized, were Edet1 = +1.40 V / ms 200 (pulse potential at which occurs only ABZ-SO oxidation) and Edet2 = 1.90 V / 200 ms (pulse potential at which the oxidation of both anthelmintic, ABZ-SO and LVM, occurs). The analytical curves showed linearity from 2.00 to 100.0 ^mol L-1 (ABZ-SO) and 0.03 to 1.00 ^mol L-1 (LVM), with LD of 1.00 ^mol L-1 and 6.0 nmol L-1 for ABZ-SO and LVM, respectively. Samples of synthetic urine doped with two different concentrations of ABZ-SO and LVM presented recoveries from 93.3 to 100%. The procedure was simple, accurate and fast, with an analytical frequency of 53 samples per hour. In the last one procedure it was developed a method for simultaneous determination of hydrochlorothiazide (HTZ) and enalapril (ENP) (antihypertensives) using a FIA-MPA system and BDD-CPT electrode. The FIA-MPA method was also proposed based on the direct determination of HTZ and indirect of ENP. The sequence application of the pulses as a function of time, were, Edet1 = +1.50 V / ms 150 (pulse potential at which HTZ occurs) and Edet2 = +1.80 V / ms 150 (pulse potential at which oxidation of both analytes (HTZ and ENP) occurs). The analytical curves presented linearity from 0.40 to 8.00 ^mol L -1 to HTZ and from 0.03 to 1.00 ^mol L-1 to HTZ and LD obtained for HTZ and ENP were 0.20 and 0.01 ^mol L-1, respectively. It was analysed three pharmaceutical commercial samples containing both analytes and the results obtained using the FIA-MPA method are in agreement with those obtained using a comparative method (HPLC) with a confidence level of 95%. The procedure was simple and fast, with an analytical frequency of 89 samples per hour.